Recovery of samarium from cobalt–samarium solution using phosphoric acid. Issue 4 (December 2015) - Onoda, Hiroaki; Kurioka, Yuki
Graphical abstract: Abstract: Cobalt–samarium alloys are generally used for producing magnets. Samarium falls under the class of rare earth elements, which are precious and expensive, because of which they are often recovered by recycling processes to save cost. There are a few reported processes for the recycling of rare earth elements; however, these processes have disadvantages, including the requirement for high temperatures and use of harmful gases. In this paper, a novel technique to recover samarium without encountering the difficulties reported in previous methods is presented. Because rare earth phosphates are the main components of rare earth ore, a novel phosphate process is suggested in this work. The cobalt–samarium solution was mixed with phosphoric acid solution and then adjusted to several pH with sodium hydroxide solution and nitric acid. The precipitates were filtered and dried. The ratio of samarium and cobalt in the precipitates and filtered solutions was estimated by the ICP (inductively coupled plasma) method. As an ideal phenomenon, samarium phosphate was filtered off, so that the filtrate contained the cationic cobalt species. The Sm/Co and P/(Co + Sm) ratios; concentrations of samarium, cobalt, and phosphoric acid; and pH were varied to study the precipitation of samarium compounds. In this work, over 99% of samarium cation was recovered from the cobalt–samarium solution using phosphoric acid. This novel process was observed to be useful for the recovery of samarium, and it may find applications in the recycling and recovery of other rare earth elements of interest.